PHYSICAL COMPOSITION OF BROILER CARCASSES FED AZOLLA JUICE THROUGH DRINKING WATER - M.A., Umbung,; Siti, N.W.; Candrawati, D.P.M.A. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
This study aims to determine the effect of azolla juice through drinking water on the physical composition of broiler carcasses and has been conducted for 2 months in Banjar Merta Kelod, Yangapi Village, Bangli District, Bali Province. The research design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replicates. Each replicate consisted of 4 broiler chickens, resulting in 64 broiler chickens. The four treatments were P0 (drinking water without azolla juice), P1 (drinking water with 2% azolla juice), P2 (drinking water with 4% azolla juice), and P3 (drinking water with 6% azolla juice). Variables observed in this study included slaughter weight, carcass percentage, meat percentage, bone percentage, subcutaneous fat percentage and skin. The data obtained were analyzed using variance analysis, if there were significant differences (P < 0.05) then continued with Duncan's multiple range test. The results showed that the slaughter weight, carcass percentage, and bone percentage of the P1, P2, and P3 treatments decreased compared to the P0 treatment, but were not statistically significantly different (P>0.05). While the percentage of meat and fat was higher than the P0 treatment, but statistically not significantly different (P>0.05). Based on the results of the study, it can be concluded that the provision of 2 -6% azolla juice in drinking water to broilers has not been able to influence the physical composition of broiler carcasses.